Civic Education as a Means of Preserving and Empowering Iko-Iko Cultural Heritage in the Sapeken Islands - Delvi Fitria Ningsih; Yulius Rustan Effendi; Andri Fransiskus Gultom (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This study examines the role of civic education as a strategic instrument in efforts to preserve and empower the Iko-Iko cultural heritage in the Sapeken Islands. Through a qualitative approach using a case study method, the study revealed that integrating local cultural values into the civic education curriculum can create synergy between strengthening national identity and preserving local wisdom. The research findings show that Iko-Iko culture-based learning not only increases students' awareness and pride in their cultural heritage but also strengthens the cultural resilience of the Sapeken community in the face of globalisation. The integrated learning model developed has succeeded in transforming civic education practices from a conventional approach to empowering contextual learning. The implementation of this model encourages the active participation of the younger generation in efforts to conserve and develop the Iko-Iko tradition as a national cultural asset. The study concludes that revitalising civic education based on local wisdom is an effective strategy in maintaining the sustainability of cultural heritage while building the character of citizens with cultural identity